A clinicopathological review of 100 cases of primary malignant tumours of the liver. Issue 8 (August 1974) - MacSween, R. N. M.
Abstract : One hundred cases of primary malignant tumour of the liver coming to necropsy in the period 1900-1969 have been reviewed. The overall tumour incidence was 0·46% of all necropsies. The overall tumour incidence in hepatic cirrhosis was 12·3%, but the corresponding male and female incidences were 17·5 and 4·4% respectively. There was no significantly increased tumour incidence in haemochromatosis. An increasing incidence of primary malignant tumours of the liver has been noted since 1940 and appears to be due to a corresponding increase in incidence of hepatic cirrhosis. Hepatocellular carcinomas outnumbered cholangiocarcinomas by 8 to 1, were more common in males than females (6 to 1), and in 77% of cases occurred in cirrhotic livers. Tumours supervened as a complication of macronodular or predominantly macronodular cirrhotic patterns.